A Roadmap Towards Integrity: A President’s Perspective Twenty Years On - Christensen Hughes, Julia (Canadian Perspectives on Academic Integrity, 2023)
In this session, I will share what prompted my original 2002-2003 study on student academic misconduct with Don McCabe, published in the Canadian Journal of Higher Education, and my reflections on what has transpired in the ensuing twenty years. Highlighting key observations from my more recent contributions (in Handbook of Academic Integrity and Academic Integrity in Canada: An Enduring and Essential Challenge), I will present a roadmap towards integrity, with implications for senior university administrators (as well as faculty and students), committed to strengthening the integrity of the academy.